INFLAMMATORY ABDOMINAL AORTIC ANEURYSM: REVIEW - Ferreira, Joana (2017)
The presence of abdominal or back pain, weight loss and elevated erythrocyte sedimentation rate is characteristic of the inflammatory abdominal aortic aneurysms. Low-grade fever is sometimes identified. Other inflammatory markers, such as white blood cell count, C reactive protein, anti-nuclear antibody and IgG4 levels can be elevated. Computed tomography is the exam of choice, showing characteristically the mantle sign. Steroids improve the symptomatology and reduce inflammation, but do not treat the aneurysm. The choice of interventions: open surgical repair or endovascular aneurysm repair can be considered according to the available expertise, patient risk factors, anatomic aneurysm criteria and presence of hydronephrosis.